Aspectos imunoendocrinológicos em adolescentes vítimas de maus-tratos na infância - Daruy Filho, Ledo (2015)
INTRODUCTION: Although the impact of childhood maltreatment (CM) are known, not only regarding clinical but psychosocial outcomes, an extensive field of study is still open to understanding the neurophysiological mechanisms mediating cause and outcome. Systems somehow connected to stress response, as the hypothalamic-pituitary-adrenal axis (HPA) and the immune system, are strong candidates to play an important role in this association. OBJECTIVE: To investigate peripheral cytokines and hormonal measures in healthy adolescents exposed to CM. METHOD: This thesis consists of three studies. The first one aims to understand the immune activation state by measuring six cytokines (IFN-Υ, IL-2, IL-4, IL-6, IL-10 and IL-17A) in adolescentes exposed and not exposed to CM. In the second study, we used hair and plasma cortisol measures to compare both groups. The third study investigated plasma copeptina in these groups. RESULTS: The first trial has showed decreased levels of IFN-Υ, IL-2, IL-4, IL-6 and IL-10 in CM adolescents. The second study an increased hair cortisol in adolescent victims of CM. This elevation was not confirmed with plasma cortisol. The third study found no correlation between plasma levels of copeptin and history of CM in these adolescents. CONCLUSIONS: These were the first studies to examine cytokines, hair cortisol and copeptin in healthy adolescent victims of CM. The results of this thesis seems to confirm a distinct immunological pattern in adolescent victims of CM. The decreased levels of cytokines found in this group may be due to a mechanism of immunosuppression secondary to HPA axis activation, confirmed by hair cortisol. The use of hair cortisol proved to be interesting for getting over the numerous biases contained in cortisol cross sampling, indicating an excellent measure of medium-term neuroendocrinologic response. Although there was no difference between groups in plasma copeptin, we consider important the emphasis in the studies with this biomarker in non-clinical populations, searching for a better understanding of the mechanisms involved in this association.